The Effect of Inflation, Interest Rates, and Exchange Rates on The Jakarta Composite Index - Wardana, Andrea Kusuma; Masdjojo, Gregorius Nazians (Jurnal Manajemen Bisnis, 2024)
The Jakarta Composite Index (JCI) is an indicator that is generally used to measure the performance of companies or issuers listed on the Indonesia Stock Exchange (IDX). This study aims to empirically test the determinants that affect JCI during the occurrence of covid 19. The variables tested in this study involve the influence of inflation, interest rates, and exchange rates on JCI. The methods used are descriptive analysis and regression analysis of panel data with the help of EViews program. Of the several models selected in this study is the Common Effect Model (CEM). The results showed that inflation had a positive and significant effect on JCI, interest rates had a negative and significant effect on JCI, exchange rates had a negative and significant effect on JCI. Inflation, interest rates, exchange rates together have a significant effect on JCI. The coefficient of determination by which the independent variable is able to explain the dependent variable is 54%.